2006
DOI: 10.1016/j.jacc.2006.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Antianginal Efficacy of Ranolazine When Added to Treatment With Amlodipine

Abstract: Ranolazine significantly reduced frequency of angina and nitroglycerin consumption compared with placebo and was well tolerated. (The ERICA [Efficacy of Ranolazine In Chronic Angina] Trial; http://clinicaltrials.gov; NCT00091429).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
223
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(241 citation statements)
references
References 26 publications
9
223
1
8
Order By: Relevance
“…This study also claims that better antianginal effects were observed with ranolazine in patients with increased frequency of angina episodes [26]. Similarly the TERISA trial showed significant reduction in angina frequency from 6.6 to 3.8 per wk after 8 wk of treatment with ranolazine 1000 mg BD compared to placebo group [27].…”
Section: Discussionmentioning
confidence: 71%
“…This study also claims that better antianginal effects were observed with ranolazine in patients with increased frequency of angina episodes [26]. Similarly the TERISA trial showed significant reduction in angina frequency from 6.6 to 3.8 per wk after 8 wk of treatment with ranolazine 1000 mg BD compared to placebo group [27].…”
Section: Discussionmentioning
confidence: 71%
“…Its anti‐ischemic effects have been demonstrated by several clinical trials 3, 4, 5, 6. Additionally, it exerts modulatory effects on ion channels that have been similarly observed after chronic amiodarone use, such as reductions in I Kr , I Ks , late I Na , and I Ca 7.…”
Section: Introductionmentioning
confidence: 94%
“…ERICA çalışmasında ise maksimal amlodipin (günde 10 mg oral) tedavisine günde iki defa 1000 mg ranolazin eklenmesinin ek yarar getirip getirmediği incelenmiştir 54 . Ranolazinin, angina sıklığını ve nitrat tüketimini anlamlı derecede azalttığı, kadın ve erkek hastalarda uzun etkili nitrat alan ve almayanlarda, 65 yas üzeri ya da altındaki hastalarda aynı derecede etkili olduğu görülmüştür.…”
Section: Ranolozinunclassified